Social relevance of Bhikhari Thakur’s plays as a coordinated form of religion and culture: धर्म व संस्कृति के समन्वित रूप में भिखारी ठाकुर के नाटकों की सामाजिक सोद्देश्यता - Ranjan, Rakesh (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
In the plays of Bhikhari Thakur, social purposefulness has been presented through a coordinated form of religion and culture. His plays are not only a means of entertainment, but also present a deep perspective on various issues of society. Thakur has prominently depicted social injustice, caste discrimination, women’s rights, and the struggle of the poor in his plays. There is a wonderful combination of religious elements and cultural traditions in his plays, which attracts the audience and forces them to think. Bhikhari Thakur’s literary contribution plays an important role in giving a new direction to the rural culture and society of Bihar. In this research paper, the efforts of social reform through his plays will be analyzed, so that their literary and social relevance can be clarified. Abstract in Hindi Language: भिखारी ठाकुर के नाटकों में धर्म और संस्कृति के समन्वित रूप के माध्यम से सामाजिक सोद्देश्यता को प्रस्तुत किया गया है। उनके नाटक न केवल मनोरंजन का साधन हैं, बल्कि समाज के विभिन्न मुद्दों पर गहन दृष्टिकोण प्रस्तुत करते हैं। ठाकुर ने अपने नाटकों में सामाजिक अन्याय, जातिगत भेदभाव, स्त्री अधिकार, और गरीबों के संघर्ष को प्रमुखता से दर्शाया है। उनके नाटकों में धार्मिक तत्व और सांस्कृतिक परंपराओं का अद्भुत मेल है, जो दर्शकों को अपनी ओर आकर्षित करता है और उन्हें सोचने पर मजबूर करता है। भिखारी ठाकुर का साहित्यिक योगदान बिहार की ग्रामीण संस्कृति और समाज को एक नई दिशा देने में महत्वपूर्ण भूमिका निभाता है। इस शोध पत्र में उनके नाटकों के माध्यम से समाज सुधार के प्रयासों का विश्लेषण किया जाएगा, जिससे उनकी साहित्यिक एवं सामाजिक प्रासंगिकता स्पष्ट हो सके। Keywords: भिखारी ठाकुर, धर्म, संस्कृति, सामाजिक सोद्देश्यता, नाटक, सामाजिक न्याय